Variants of creating heterotopic and orthotopic PDX models of human colorectal cancer - A. A. Kiblitskaya; A. Y. Maksimov; A. S. Goncharova; Ye. M. Nepomnyashchaya; Ye. Y. Zlatnik; G. Y. Yegorov; Ye. A. Lukbanova; Ye. V. Zaikina; A. V. Volkova (Бюллетень сибирской медицины)
Aim. To create heterotopic and orthotopic patient-derived xenograft (PDX) models of colorectal cancer (CRC) by transplantation of patient’s tumor samples into immunodeficient BALB / c Nude mice.Materials and methods. The study was performed on 15 female BALB / c Nude mice aged 6–8 weeks weighing 21–25 g. All animals underwent transplantation of the tumor material obtained from CRC patients into the following sites: heterotopic transplantation (under the skin of the thigh and into the omentum), orthotopic transplantation (into the descending and ascending colon and into the cecum). Weight and general condition of the animals and the size of the tumor nodule had been monitored for 80 days. The success of each model was assessed by the degree of engraftment, the dynamics of tumor growth, and the reproducibility of histopathologic characteristics. At the end of the experiment, the animals were euthanized by cervical dislocation.Results. 100% survival of the animals and similar tumor growth dynamics in the xenograft models were observed throughout the experiment. The analysis of histologic specimens obtained from the xenografts and patient’s tumor showed their correspondence to moderately differentiated intestinal adenocarcinoma. The main advantages and disadvantages of different variants of PDX models were described.Conclusion. Heterotopic and orthotopic PDX models reproduce the morpho-histologic characteristics of human tumors and demonstrate stable growth dynamics. Therefore, they are a suitable tool for the development, testing, and validation of potential anticancer drugs.